Pricing Strategy and Pricing Determinant Factors in Sharing Logistics - Farmaciawaty, Desy Anisya; Prasetyo, Ahmad Danu; Larasati, Niken; Inggis, Raka Achmad; Putri, Novialita Ayu C. Wibowo; Mulyono, Nur Budi (SBM ITB, 2021)
Abstract. There is a significant change in our current business practices where the change leads the mainstream business practice into a new concept: Sharing Economy. In this research, the sharing economy will be narrowed down to a specific topic called sharing logistics. This research aims: (1) to identify the determinants that are perceived as a priority by customers in logistics service, (2) to explore the pricing method suitable for sharing logistic companies based on priority determinants, which are previously identified. To arrive at the objectives of the research, many works of literature were reviewed related to the matter of determinants and pricing strategies in the logistics service industry and related to the concept of sharing economy. Primary data was also collected through an interview with the expert of the leading logistic service company in Indonesia. In addition, the analytical hierarchy process (AHP) was conducted as well to find the proportion that represents determinants’ priority based on the perspective of the customers of logistic service providers and academic researchers. Hopefully, by identifying the determinants that are perceived as a priority by customers in logistics service, and with its appropriate pricing method, companies that run their business in logistics sharing will have a proper pricing method guideline in the first place.Keywords: Sharing economy, sharing logistics, pricing method, determinants of logistics service, analytical hierarchy process Abstrak. Saat ini terdapat perubahan signifikan terhadap praktik bisnis yang mengakibatkan munculnya konsep baru yaitu Sharing Ecpnomy. Dalam penelitian ini, sharing economy yang akan diteliti dipersempit ke topik tertentu, yaitu sharing logistics. Tujuan dari penelitian ini adalah: (1) untuk mengidentifikasi determinan yang dipersepsikan sebagai prioritas oleh pelanggan dalam layanan logistik, (2) untuk mengeksplorasi metode penetapan harga yang sesuai untuk perusahaan sharing logistics berdasarkan determinan prioritas, yang telah diidentifikasi sebelumnya. Untuk sampai pada tujuan penelitian, dilakukan tinjauan literatur terkait dengan masalah determinan dan strategi penetapan harga di industri jasa logistik serta tinjauan terhadap konsep sharing economy. Pengumpulan data primer dilakukan melalui wawancara dengan pakar dari perusahaan jasa logistik terkemuka di Indonesia. Selain itu, metode analytical hierarchy process (AHP) juga dilakukan untuk mengetahui proporsi yang mewakili prioritas determinan berdasarkan perspektif pelanggan penyedia jasa logistik dan peneliti akademis. Diharapkan dengan mengidentifikasi determinan yang dianggap sebagai prioritas oleh pelanggan dalam layanan logistik, dan dengan metode penetapan harga yang tepat, perusahaan yang menjalankan bisnisnya dalam logistics sharing akan memiliki pedoman metode penetapan harga yang tepat. Kata kunci: Sharing economy, sharing logistics, metode penetapan harga, determinan layanan logistik, analytical hierarchy process.